Early Molecular Diagnosis and Comprehensive Treatment of Oral Cancer - Po-Chih Hsu; Jen-Hsuan Huang; Chung-Che Tsai; Ya-Hsuan Lin; Chan-Yen Kuo (Current Issues in Molecular Biology)
Oral squamous cell carcinoma (OSCC), a major subtype of head and neck squamous cell carcinoma (HNSCC), is a significant global health burden owing to its late-stage diagnosis and poor prognosis. Recent advancements in molecular biology, genomics, and imaging have transformed the landscape of OSCC diagnosis and treatment. This review provides a comprehensive synthesis of early molecular diagnostic strategies, including biomarker discovery using next-generation sequencing, liquid biopsy, and salivary exosomal microRNAs. In addition, we highlight the emerging role of non-invasive optical imaging technologies and their clinical integration for improved surgical precision and early lesion detection. This review also discusses evolving therapeutic approaches, including immunotherapy, neoadjuvant chemotherapy, and patient-centered multimodal regimens tailored through molecular profiling. We emphasized balancing therapeutic efficacy with the quality of life in patients undergoing chemoradiotherapy. The convergence of multi-omics, artificial intelligence, and precision medicine holds promise for revolutionizing early detection and personalized treatment of OSCC, ultimately improving patient survival and clinical outcomes.